EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA PATTONGKO KECAMATAN SINJAI TENGAH KABUPATEN SINJAI - Nasir (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2024)
This study aims to evaluate the effectiveness of the management of Village Fund Allocation (ADD) in improving physical development in Pattongko Village, Central Sinjai District, Sinjai Regency. Physical development funded by ADD is expected to be able to improve the quality of village infrastructure, such as roads, irrigation canals, and other public facilities, which has a direct impact on community welfare. The research method used is qualitative descriptive, with data collection through interviews, observations, and documentation. The informants consisted of village heads, village officials, and local community leaders. The results of the study show that the management of ADD in Pattongko Village has been quite effective, characterized by community participation in the planning and implementation of development. However, there are still several challenges, such as the limited capacity of village officials in administrative management and delays in disbursement of funds. However, the physical development carried out, especially in the agricultural infrastructure sector, has had a positive impact on increasing community accessibility and productivity. This study suggests increasing training for village officials and optimizing the role of the community in supervising development programs.